Ukrainian dialect phraseologism lapati zaicya and its other Slavic parallels (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the inner shape of Ukrainian dialect phraseologism lapati zaicya 'to say (to do) nonsense' on the background of similar in structural and semantic relation of the phrases in the related Slavic languages. The archaic symbolism of the word- component zayac, which is characterized with ambivalent characteristics is set in this article.
Keywords: phraseology; diachronic analysis; structural and semantic model; word-symbols; folk spiritual culture